2020
DOI: 10.1038/s41380-020-00912-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of FMRP targets with psychiatric disorders

Abstract: Genes encoding the mRNA targets of fragile X mental retardation protein (FMRP) are enriched for genetic association with psychiatric disorders. However, many FMRP targets possess functions that are themselves genetically associated with psychiatric disorders, including synaptic transmission and plasticity, making it unclear whether the genetic risk is truly related to binding by FMRP or is alternatively mediated by the sampling of genes better characterised by another trait or functional annotation. Using publ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 99 publications
(198 reference statements)
3
23
1
Order By: Relevance
“…Gene ontology analyses of brain-derived FMRP targets confirm an overrepresentation of genes involved in functions related to synaptic activity, plasticity, development, and anatomy [19, 52, 58], consistent with studies of FMRP function. The proteins they encode include both presynaptic and postsynaptic components.…”
Section: Fmrp Targetssupporting
confidence: 70%
See 3 more Smart Citations
“…Gene ontology analyses of brain-derived FMRP targets confirm an overrepresentation of genes involved in functions related to synaptic activity, plasticity, development, and anatomy [19, 52, 58], consistent with studies of FMRP function. The proteins they encode include both presynaptic and postsynaptic components.…”
Section: Fmrp Targetssupporting
confidence: 70%
“…A set of FMRP target mRNAs derived from a study of mouse cortical polyribosomes [19] have been recurrently highlighted in the literature due to their enrichment for genes associated with an array of psychiatric disorders. Through large-scale genome-wide association studies, these 842 FMRP targets have been shown to be genetically associated with schizophrenia [161, 162], autism [166], major depressive disorder [167], and bipolar disorder [58]. In addition to the risk conferred from common variation, this gene set is enriched for rare variants from patients with schizophrenia [168-171], autism [172], and bipolar disorder [173]; de novo variants from patients with schizophrenia [174] and autism [175-177]; and to a lesser extent copy number variants from patients with schizophrenia [178-180].…”
Section: Fmrp and Fmrp Targets In Psychiatric Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent meta-analytic GWAS of common variants in schizophrenia included an additional 5220 schizophrenia cases and 18,823 controls and identified 145 independent loci significantly associated with schizophrenia [ 7 ]. Schizophrenia-associated SNPs were enriched for genes that are intolerant to mutation, genes involved in synaptic transmission, and genes that are targets of the fragile X mental retardation protein (FMRP), which is known to regulate the protein-level expression of genes involved in brain development and synaptic plasticity [ 8 ]. Together, these seminal studies provided compelling evidence that common risk variants for schizophrenia converge onto neuronal and synaptic gene-sets.…”
Section: Genetic and Epigenetic In Sczmentioning
confidence: 99%